PENGUJIAN DECISION MAKING MODEL DENGAN MEDIASI FINANCIAL LITERACY DAN RISK TOLERANCE DALAM MEMPREDIKSI PERILAKU INVESTASI MAHASISWA - Haq, Rizki Azizul; Utami, Budi Barata Kusuma (Transpublika Publisher, 2024)
This study aims to test the investment decision model among college students by integrating financial literacy and risk tolerance as mediating variables. The sample in this study were students who had invested. The data analysis technique used in this research is Structural Equation Modeling (SEM). Testing includes measurement models (outer model) and structural models (inner model). The results of this study indicate that mental accounting, herding behavior, and risk preference directly affect investment interest. Risk tolerance can mediate the effect of herding behavior on investment interest. In addition, financial literacy can mediate the influence between mental accounting and risk preference on investment interest. Furthermore, interest is the dominant factor in driving investment decisions. This research contributes theoretically by expanding the investment decision-making model, especially among students.